Collective labor supply of native dutch and immigrant households in the Netherlands - Chris van Klaveren; Bernard M. S. van Praag; Henriëtte Maassen van den Brink (Center for Economic Studies and ifo Institute (CESifo), 2009)
We estimate a collective time allocation model, where Dutch, Surinamese/Antillean and Turkish households behave as if both spouses maximize a household utility function. We assume that paid labor and housework are the endogenous choice variables and furthermore consider household production. Surinamese/Antillean and Turkish women differ from Dutch women because they value (joint) household production more in their utility function. Surinamese/Antillean and Turkish men, on the other hand, value joint household production less then Dutch men. Turkish households are the more traditional households, in the sense that the woman is more oriented on household production, while the man is oriented on paid labor. It is often believed that the bargaining power of women in more traditional households is relatively low, but our estimation results do not support this idea. In general, the wage elasticities of Dutch, Turkish and Surinamese/Antillean households are comparable. Men and women replace housework hours by paid labor if their hourly wage rate increases but do the opposite when the hourly wage rate of the partner increases.
Keywords: D12; D13; J22; 330; collective model; labor supply; child care; Arbeitsangebot; Haushaltsökonomik; Hausarbeit; Lohn; Preiselastizität; Vergleich; Bevölkerung; Migranten; Niederlande